Effect of Orally-administered Silver Nanoparticles (Ag-NPs) on Some Biochemical Parameters in Kidney of Rats - H. Kh. Ismail 1 , A. A. AlKshab2 , A. A. AL-Baker2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research evaluated the oral administration of silver nanoparticles on the tissue morphology andbiochemical parameters of kidneys in rats, using (0.2 and 0.4) mg/kg B.W for four days and 0.08,0.008 mg/kg weight For 30 days . The result showed significant increase in the level of serum creatinine and serumurea for animals treated with silver nanoparticles relative to the control at the dose of (0.08 and 0.008) mg/kgB.W for 30 days. As for the histological study of kidneys showed sever changes at the dose (0.08 and 0.008)mg/kg compared with the dose 0.2 and 0.4 mg/kg for 4 day which include infiltration of inflammatory cells,haemorrhage, and degenerated and necrotic changes in renal tubules epithelium.